Anterior–posterior pattern formation in ciliates. (5th February 2022) - Cole, Eric; Gaertig, Jacek
Abstract: As single cells, ciliates build, duplicate, and even regenerate complex cortical patterns by largely unknown mechanisms that precisely position organelles along two cell‐wide axes: anterior–posterior and circumferential (left–right). We review our current understanding of intracellular patterning along the anterior–posterior axis in ciliates, with emphasis on how the new pattern emerges during cell division. We focus on the recent progress at the molecular level that has been driven by the discovery of genes whose mutations cause organelle positioning defects in the model ciliate Tetrahymena thermophila . These investigations have revealed a network of highly conserved kinases that are confined to either anterior or posterior domains in the cell cortex. These pattern‐regulating kinases create zones of cortical inhibition that by exclusion determine the precise placement of organelles. We discuss observations and models derived from classical microsurgical experiments in large ciliates (including Stentor ) and interpret them in light of recent molecular findings in Tetrahymena . In particular, we address the involvement of intracellular gradients as vehicles for positioning organelles along the anterior‐posterior axis.